"Water-in-ionic liquid" solutions towards wide electrochemical stability windows for aqueous rechargeable batteries. (10th February 2018) - Zhang, Yonglai; Ye, Ruijie; Henkensmeier, Dirk; Hempelmann, Rolf; Chen, Ruiyong
Abstract: Several hydrophilic ionic liquids dissolved in water with different molalities are studied as "water-in-ionic liquid" supporting electrolytes. They exhibit wide electrochemical stability window from 3 to 4.4 V, high ionic conductivities and good flowability, making them promising supporting electrolytes for aqueous high-voltage rechargeable batteries. In such supporting electrolytes, enhanced redox activities of lithium insertion/extraction in anodic TiO2 film at low negative potential and Fe 3+ /Fe 2+ couple at moderate positive potential were observed. Cyclability of an aqueous TiO2 /Fe 2+ hybrid battery is demonstrated with a voltage of 1.7 V.